Open code and appropriation of collaborative dynamics by Google Inc - Vinicius, Gerbasi Aleixo [UNESP] (2019)
Innovation on computer programs is a result of the private appropriation of information. We analyses the factors by which the Android operating system, owned by Google Inc., advocates open source. We ask how the sharing model appropriates the innovation and collaboration of the workers. The methodology is characterized by the theoretical-analytical survey, analysis of company's website and interviews. To limit access to knowledge is not a good choice. Patenting parts of the code gives it a way to dominate and subsume the work, which is highly creative. In addition, it allows the movement of innovation flows among a wide diversity of workers.